Representasi Nilai-Nilai Islam dalam Podcast Login (Analisis Isi Model Philipp Mayring) - Shaliha, Faradiba; Soiman; Soiman, Soiman (Universitas Islam Negeri Raden Intan Lampung, 2025)
The increasing use of digital media as a means of preaching is the impact of technological developments that encourage preachers to utilize various digital platforms to facilitate preaching activities. One of the popular platforms used is YouTube, which provides various preaching content. One of the preaching contents on this platform is the